EFEKTIVITAS E-LKPD IPAS BERBASIS DISCOVERY LEARNING MENGGUNAKAN THUNKABLE UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DASAR PESERTA DIDIK KELAS IV - Hendra, Putra You; Ronaldo, Gito; Nurhayati, Nurhayati; Rohman, Fatkhur; Pramudiyanti, Pramudiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effectiveness of the E-LKPD product based on discovery learning using Thunkable to improve the science process skills of fourth-grade students. This study is a quantitative research utilizing the Quasi-Experimental Design method. The sampling technique used is saturated sampling, where the entire population is taken as the research sample, consisting of fourth-grade students. The data collection method employed is observation, conducted before and after using the product to measure the students' science process skills. The results of the study indicate that the use of the E-LKPD IPAS based on discovery learning using Thunkable has a high effectiveness in improving the basic science process skills of fourth-grade students, with an N-Gain test result of 0.728.